Darcy – weish bach friction factor through porous rectanguler open – channels - Venkateshwarlu, A (Journal of Experimental Sciences, 2012)
Open channel flows widely occur in the design of irrigation canal net works.Most of the investigation on open channel flows are experimental studies only.This may be due to geometric complexity of channels and channel networks.The present paper deals with an analytical investigation on the flow through an open porous straight channel of rectangular cross-section under a constant pressure gradient.The momentum equation takes care of the convective acceleration and the viscous stresses generated in the flow region. The basic flow equation is solved (i) analytically employing Fourier series technique yielding exact solution and (ii) approximately by Galerkin technique that would facilitate fast numerical computation of the result. Expression for the Darcy-Weish Bach Friction factor has been computed for a wide spectrum of the values of the channel depth and porosity coefficient of the flow medium and its variation graphically illustrated. The results obtained by the two methods support each other.